Optimal Indirect Tax Revenues and Economic Growth in Sudan Economy: A Threshold Regression Approach - Arabi, Khalafalla Ahmed Mohamed; Elbeely, Khalid Hassan (European Scientific Journal, ESJ, 2019)
Indirect taxes play a fundamental role in revenue collection in Sudan. This role is under investigation by estimating an optimum level beyond which they make vulnerable the acceleration of economic growth. A threshold regression was used for estimation which covers the period 1970 – 2017. The model contains real GDP (Y) as the dependent variable and indirect taxes as a threshold variable. The unemployment rate (UR), the external gap (GAP2), and the real effective exchange rate (REER) are the non-threshold variables. The main research findings indicate that the average indirect tax ratio is more than three times the direct tax ratio and constitutes about 55.3% of the total revenue collection compared to 18% of the direct tax. These findings suggest that the optimum threshold is 7.46% above which indirect taxes exert a negative impact on economic growth. It is clear that resorting to indirect taxes fosters the maximum economic growth at the threshold that corresponds to the year 1982. This year is considered to be the most economically stable year (elected as a base year). Here the non-threshold variables i.e. external gap represents 0.03% of its mean value, while real exchange rate and employment rate are less than their mean values. This paper focuses on restructuring the tax system which is highly recommended to shift the balance in favor of direct taxes so as to curb price rises, attain social and economic balance, and reduce income inequality. Economic policies have to be focused on tackling unemployment especially among young graduates and disguised unemployment. Here, monitory policy can stimulate demand and put the economy back on track, as well as a fiscal policy through taxation and government spending. A favorable economic environment conducive for investment and jobs creation ought to be one of the priorities. Job description and irradiation of nepotism can help much in reducing unemployment. Export diversification and improved range of merchandized, recapitalization of the export-import (EXIM) bank for smooth credit provision, revision of rules & tariffs, creation of single window for customs clearance, and the stable exchange rate should be the main concern of the government.